2022
DOI: 10.1002/admi.202200614
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Ti3C2Tx MXene/Poly(Styrene‐Methacrylic Acid)@Polypyrrole Nanospheres/Thermoplastic Polyurethane Electrospinning Membrane for High Sensitivity Pressure Sensing and Pressure‐Electrothermal

Abstract: wearable electronics and are classified into four categories according to their sensing mechanisms: piezoresistive, capacitive, piezoelectric, and triboelectric. [6][7][8][9] Compared to the other pressure sensors, the piezoresistive pressure sensor constructed from flexible substrates and conductive materials is considered the most promising for industrialization. [10] This benefit from the fact that the piezoresistive pressure sensor has the advantages of reliable sensing performance, low costs, less suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…32 The vast majority of current electrostatic spinning technologies are used to fabricate flexible substrates for sensitive layers in flexible sensors. After electrospinning the substrate material into a nanofiber film, the active conductive filler is then doped onto the flexible substrate by in situ polymerization, [33][34][35] vacuum evaporation, 36 sputtering, [37][38][39][40] chemical deposition, extraction, 36,41,42 electrostatic spraying, 43 and dip coating [44][45][46][47][48][49] to form a composite nanofiber film with conductive activity. Structural properties of flexible substrates provide high sensitivity of such composite nanofiber membrane.…”
Section: The Principle Of Electrostatic Spinning and The Main Means O...mentioning
confidence: 99%
See 1 more Smart Citation
“…32 The vast majority of current electrostatic spinning technologies are used to fabricate flexible substrates for sensitive layers in flexible sensors. After electrospinning the substrate material into a nanofiber film, the active conductive filler is then doped onto the flexible substrate by in situ polymerization, [33][34][35] vacuum evaporation, 36 sputtering, [37][38][39][40] chemical deposition, extraction, 36,41,42 electrostatic spraying, 43 and dip coating [44][45][46][47][48][49] to form a composite nanofiber film with conductive activity. Structural properties of flexible substrates provide high sensitivity of such composite nanofiber membrane.…”
Section: The Principle Of Electrostatic Spinning and The Main Means O...mentioning
confidence: 99%
“…It was shown that PANI fibers doped with hydrochloric acid were able to produce high electrical conductivity of about 20 S cm −1 and exhibited 10ppm detection sensitivity to ammonia. Cheng et al 42 enhanced the degree of contact resistance variation of the sensor under pressure loading by building nanoscale geometric microstructures on a flexible substrate in order to make further breakthroughs in the sensitivity of flexible pressure sensors. The main design idea was to pump PPy nanomicrospheres onto a thermoplastic polyurethane electrospun membrane by decompression pumping to form an octopus tentacle-like nanostructure, and then spray on MXene dispersion to construct a multilayer conductive network with nanosphere structure (Figs.…”
Section: Electrospun Materials and Structural Design Of Sensitive Layersmentioning
confidence: 99%
“…Flexible piezoresistive micro-pressure sensors have promising applicable potential because of their simple structure, facile materials preparation, low cost, and other merits. [125][126][127] Graphene, carbon nanobers and carbon nanotubes (CNTs) are the most common conductive materials for preparing piezoresistive pressure sensors. 128 These sensors have high sensitivity, great stretchability, good exibility, and excellent stability, and are suitable for micro-pressure detection in different application scenarios.…”
Section: Triboelectric Micro-pressure Sensorsmentioning
confidence: 99%
“…With the rapid rise in wearable electronic devices, flexible sensors are growing by leaps and bounds and are showing substantial applications in various fields, such as human motion monitoring, artificial intelligence robotics, and human–computer interaction. Crack-structured strain sensors with conductive materials coated on a flexible substrate have become a widely used strategy ,, with advantages such as easy fabrication and short response time. However, it is still a challenge to combine high sensitivity and high tensile range due to the resistance change of crack-based sensors based on the breakage and reversion of the conductive network. , High sensitivity requires the sensor to undergo violent fracture or recovery of the conductive network at a weak stretch, which makes it impossible to maintain the conductive network at large strains .…”
Section: Introductionmentioning
confidence: 99%